A new approach to measure the outcomes of university mergers. (2017) - Zineldin, Mosad; Vasicheva, Valentina
Strategic alliances and mergers (SAMs) are well-known organisational instruments to increase the pool resources, competitive advantages, strengthen the power and strategic positioning for achieving synergy effects (SEF). This study aims to explore and measure the possible SEF of mergers using the 5Qs approach. Data for this study was collected from questionnaires. The data was analysed using a multiple regression model in order to test the effect of the independent variables related to mergers and the dependent variable of SEF. The results indicate that not all qualities were significant but the infrastructure-oriented construct (INFRA) and the process-oriented construct (PROC) are the most significant in the regression models for obtaining better SEF of the merger relationship. The study extracts the valuable lessons that might help others to effectively utilise mergers and strategic alliances between corporations and higher education institutions.